Molecular Dynamics Simulation of the Influenza A(H3N2) Hemagglutinin Trimer Reveals the Structural Basis for Adaptive Evolution of the Recent Epidemic Clade 3C.2a - Yokoyama, Masaru; Fujisaki, Seiichiro; Shirakura, Masayuki; Watanabe, Shinji; Odagiri, Takato; Ito, Kimito; Sato, Hironori (Frontiers in Microbiology, 2017)
Influenza A(H3N2) has been a major cause of seasonal influenza in humans since 1968, and has evolved by antigenic drift under the constantly changing human herd immunity. Increasing evidence suggests that the antigenic change occasionally occurred concomitant with the alterations of the N-glycosylation site profile and hemagglutination activity of the virion surface protein hemagglutinin (HA). However, the structural basis of these changes remains largely unclear. To address this issue, we performed molecular dynamics simulations of the glycosylated HA trimers of the A(H3N2), which has a novel pattern of Asn-X-Ser/Thr sequons unique in the new A(H3N2) epidemic clade 3C.2a and is characterized by attenuated ability to agglutinate nonhuman erythrocytes. Comparison of the equilibrated structures of the glycosylated HA trimers with and without the 3C.2a-specific mutations reveals that the mutations could induce a drastic reduction in the apical space for the ligand binding via glycan-shield rearrangement. The results suggest that the 3C.2a strain has evolved an HA structure that is advantageous for evading pre-existing antibodies, while also increasing the ligand binding specificity. These findings have structural implications for our understanding of the phenotypic changes, evolution, and fate of influenza A(H3N2).